From Computational Thinking to Computational Participation in K-12 Education. - Kafai, Yasmin B. (Communications of the ACM, 2016)
The author offers an argument that computational thinking should be understood as computational participation in K-12 education. Topics include the nature of student interest in computer programming, the creation of applications in a communal context by students, and the need for broader participation in computer science education by K-12 students.